Bone marrow adipose tissue: Role in bone remodeling and energy metabolism - Tencerova, Michaela; Ferencakova, Michaela; Kassem, Moustapha (Best practice & research. Clinical endocrinology & metabolism, 2021)
Bone marrow adipose tissue (BMAT) has been considered for several decades as a silent bystander that fills empty space left in bone marrow following age-related decrease in hematopoiesis. However, recently new discoveries revealed BMAT as a secretory and metabolically active organ contributing to bone and whole-body energy metabolism. BMAT exhibits metabolic functions distinct from extramedullary adipose depots, relevant to its role in regulation of energy metabolism and its contribution to fracture risk observed in metabolic bone diseases. This review discusses novel insights of BMAT with particular emphasis on its contribution to the regulation of bone homeostasis. We also discuss the role of BMAT in regulation of fuel utilization and energy use that affect skeletal stem cell functions.
Keywords: bone marrow adipose tissue; energy metabolism; metabolic pathways; energetický metabolismus; Bone Remodeling; remodelace kosti; kosti a kostní tkáň; Bone and Bones; Energy Metabolism; bone marrow mesenchymal stem cells; Bone Marrow; Humans; kostní dřeň; tuková tkáň; lidé; Adipose Tissue